Evoked hypoalgesia is accompanied by tonic pain and immune cell infiltration in the dorsal root ganglia at late stages of diabetic neuropathy in mice - Agarwal, Nitin; Helmstädter, Johanna; Rangel Rojas, Daniel; Bali, Kiran Kumar; Gangadharan, Vijayan; Kuner, Rohini (Molecular pain, 2018)
Diabetic peripheral neuropathy is a major debilitating late complication of diabetes, which significantly reduces the quality of life in patients. Diabetic peripheral neuropathy is associated with a wide spectrum of sensory abnormalities, where in loss of sensation or hypoalgesia to applied external stimuli is paradoxically accompanied by debilitating tonic spontaneous pain. In numerous studies on animal models of diabetic peripheral neuropathy, behavioural measurements have been largely confined to analysis of evoked withdrawal to mechanical and thermal stimuli applied to dermatomes, whereas spontaneous, on-going pain has not been widely studied. In the Streptozotocin model of type 1 diabetes, we employed the Conditioned Place Preference test to assess tonic pain. Our results indicate that both phases, that is, early evoked hypersensitivity (i.e. 5-7 weeks post-Streptozotocin) as well as late stage hypoalgesia (i.e. 17-20 weeks post-Streptozotocin) are accompanied by significant tonic pain in mice with diabetic peripheral neuropathy. We also report on the temporal relation between on-going pain and neuropathological changes in the dorsal root ganglia of mice with diabetic peripheral neuropathy up to 6 months post-Streptozotocin. Neither early hypersensitivity nor late hypoalgesia were associated with markers of cellular stress in the dorsal root ganglia. Whereas significant neutrophil infiltration was observed in the dorsal root ganglia over both early and late stages post-Streptozotocin, T-cell infiltration in the dorsal root ganglia was prominent at late stages post-Streptozotocin. Thus, longitudinal analyses reveal that similar to patients with chronic diabetic peripheral neuropathy, mice show tonic pain despite sensory loss after several months in the Streptozotocin model, which is accompanied by neuroimmune interactions in the dorsal root ganglia.
Gesehen am 10.05.2019